2012
DOI: 10.1073/pnas.1116431109
|View full text |Cite
|
Sign up to set email alerts
|

PGRP-LB is a maternally transmitted immune milk protein that influences symbiosis and parasitism in tsetse’s offspring

Abstract: Beneficial microbe functions range from host dietary supplementation to development and maintenance of host immune system. In mammals, newborn progeny are quickly colonized with a symbiotic fauna that is provisioned in mother's milk and that closely resembles that of the parent. Tsetse fly (Diptera: Glossinidae) also depends on the obligate symbiont Wigglesworthia for nutritional supplementation, optimal fecundity, and immune system development. Tsetse progeny develop one at a time in an intrauterine environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 42 publications
2
85
0
Order By: Relevance
“…In laboratory studies, Wigglesworthia density has been shown to influence host traits for resistance to trypanosome infections through the induction of a host immune protein, peptidoglycan recognition protein LB (PGRP-LB) (66). The same host factor, PGRP-LB, was also shown to exhibit antibacterial activity in vitro (66,67). Thus, the various Wigglesworthia densities found in natural populations could impact the vector competence of these individuals and species and the ability of other microbes to survive in their guts.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory studies, Wigglesworthia density has been shown to influence host traits for resistance to trypanosome infections through the induction of a host immune protein, peptidoglycan recognition protein LB (PGRP-LB) (66). The same host factor, PGRP-LB, was also shown to exhibit antibacterial activity in vitro (66,67). Thus, the various Wigglesworthia densities found in natural populations could impact the vector competence of these individuals and species and the ability of other microbes to survive in their guts.…”
Section: Discussionmentioning
confidence: 99%
“…PGRP-LB is maternally transmitted via milk secretions to developing offspring and is produced by adult flies only after their first blood meal (123). This protein also exhibits trypanocidal activity (123). Therefore, higher levels of PGRP-LB may aid in the refractory nature of older, nonteneral flies with respect to trypanosome infection.…”
Section: Understanding the Tsetse Holobiont For Enhanced Vector Controlmentioning
confidence: 99%
“…The host pathogen recognition protein PGRP-LB, which scavenges peptidoglycan, thus preventing immune deficiency (IMD) signaling pathway stimulation, is intimately associated with maintaining the Wigglesworthia symbiosis (56,123). PGRP-LB is maternally transmitted via milk secretions to developing offspring and is produced by adult flies only after their first blood meal (123). This protein also exhibits trypanocidal activity (123).…”
Section: Understanding the Tsetse Holobiont For Enhanced Vector Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in W. morsitans population density were also observed following vitamin administration, possibly either due to symbiont recognition of a decreased need or, more likely, particularly in light of the drastic genome reduction of W. morsitans, through host modulation. In support of more-probable host-mediated control, components of the tsetse immune system, notably the peptidoglycan recognition protein (PGRP-LB), have been shown to control the abundance of the W. morsitans symbiont (52,53). In further support of host influence, modeling and experimental studies of the Buchnera and aphid symbiosis suggest that alterations in nutritional phenotypes may be directed by variation in the host's capacity to supply precursors to symbionts rather than differences in symbiont genomic capabilities (15,22,51).…”
mentioning
confidence: 99%